Information Ethics and its Implications for Library and Information Professionals: A Contemporary Analysis (Philosophy and Progress, 2014)
Information ethics provides an ethical framework for the information professionals for carrying out various information related works like acquiring, storing, processing and using of information. This has become vitally important in modern times, which has been dubbed as information age, because of the central role played by information in the socio-economic development of world nations. This also poses unique challenges for the library and information professionals, because the emergence of an ICT-driven information society has made their job much more challenging than before. This article explores the key questions related to information ethics and, in the light of codes of ethics promoted by national and international information organizations, discusses how information professionals could discharge their duties in an ethical and morally justifiable manner.DOI: http://dx.doi.org/10.3329/pp.v51i1-2.17677